Preclinical impact of blueberry supplementation in healthy and prediabetic conditions - Focus on gut microbiota and hepatic mitochondria bioenergetics - Nunes, Sara Raquel Ramalho Pereira (2022)
Tese de Doutoramento em Ciências Farmacêuticas, Farmacologia e Farmacoterapia, apresentada à Faculdade de Farmácia da Universidade de Coimbra.